Cooperation and Competition: The Comparative Assessment of Tribal Dynamics in the Marginal Landscapes of the Wadi el-Hasa, in west-central Jordan in the Early Bronze and Iron ages - Bulent Arikan (Traces in Time, 2011)
The issue of emergent social complexity has long been debated in the anthropological literature. In the eastern Mediterranean context, the archaeological discussions of social complexity focused largely on societies that showed centralized administration, hierarchic social formations, and large urban centers in temperate parts of the region. For the marginal landscapes in the eastern Mediterranean, such as semi-desert regions, scholars have long denied social complexity on the basis of lack of attributes listed in traditional frameworks of complexity. Recently however, alternate models of complexity have been developed for tribal societies following heterarchy and corporate mode of complexity. In these models, the concepts of group fusion (i.e., cooperation) and fission (i.e., competition) have significant roles and they need to be examined in more detail, especially about how we can identify these group dynamics in the archaeological record, specifically in the settlement systems. This article focuses on the Early Bronze I-III (ca. 3,500-2,400 BC) and the Iron Age (ca. 1,200-500 BC) of the Wadi el-Hasa, in west-central Jordan, for the evolution of settlement systems as a result of tribal cooperation/competition strategies and the emergence of long-distance trade, which allowed tribes not only to thrive economically but also gain political significance in a marginal landscape in the southern Levant. The use of relatively new analytical methods in archaeology, such as the geographical information systems, for assessing temporal changes in spatial distribution of sites, identifying trade routes, determining the impacts of long-distance trade and other socio-political events in the region on the settlement systems of the Hasa has been discussed.